Mehr Europa wagen!: Zukunftsbilder als Lösungsansatz für eine Union - Brüssel, Christoph; Döring, Walter; Götze, Lenno, M.A. (Tectum Verlag, 2023)
We need a strong European Union to face the numerous crises and challenges as well as the resulting changes and transformations in the 21st century. A critical examination and an open discussion about existing facts, future developments and approaches to solutions are indispensable.Authors from different fields, with different backgrounds and differentiated orientations, analyses and perspectives were invited to present their respective approaches. The result is a valuable and pluralistic publication on different visions of the future of the European Union.With contributions byJean Asselborn | Albert Berner | Thomas Borer | Christoph Brüssel | Walter Döring | Benita Ferrero-Waldner | Sigmar Gabriel | Lenno Götze | Franz-Theo Gottwald | Friederike Haupt | Reinhard Hüttl | Volker Kronenberg | Cedric Mössner | Jivka Ovtcharova | Franz Josef Radermacher | Andreas Rebetzky | Jochen Sautermeister | Burkhard Schwenker | Norbert Streveld | Gerhard Sturm | Anabel Ternès | Reinhold Würth | Torsten Wulf